Local initiatives for green space using Poland’s Village Fund: evidence from Lodzkie voivodeship - Feltynowski, Marcin (Bulletin of Geography. Socio-economic Series, 2020)
Poland’s Village Fund (Fundusz Sołecki) is an instrument operating at the level of the so-called sołectwo, into which local-administration units known as gminas may be further sub-divided. These are therefore auxiliary administrative units in rural areas whose receipt of means from the Fund in question allows for the activation of local communities. Against that background, the research detailed here sought to examine Village Fund by reference to the greenspace-related projects pursued using it in the rural gminas of Łódzkie Voivodeship. Additional aspects are the classification of the tasks carried out, presentation of the statistical analysis applied, and consideration of the breakdown obtained for indicators relating to the share of funds allocated to green areas – by reference to the properties of the normal distribution curve.